A dichotomy of domestic and academic pathways: challenges of motherhood in an international doctoral program on land science. Issue 1 (2nd January 2022) - Velander, Sara; Silva Martinelli, Fernanda; Idam Sari, Dewi; Ali, Fatima; Biber-Freudenberger, Lisa
ABSTRACT: Dichotomies emerge among early-career land scientists when balancing their career goals with family obligations, exhibiting differences in gender and regions. Through on-line surveys, we examined the interconnection between family obligations and doctoral performance through a gender lens on an international sample of doctoral students. The analysis of the findings indicated that more women than men in the doctoral program were responsible for family obligations, with mothers experiencing a prolonged duration of completing their doctorates and a lower publication rate. Majority of the respondents, primarily women from the Global North, decided not to be parents due to anticipated challenges with maintaining a work-life balance exacerbated by traditional gender roles, limited financial support for childcare, and high demands of academia. The constraints of early-career land scientists, particularly mothers from the Global South living apart from relatives, need to be addressed for institutes to strengthen international gender equality in land science.